A method for preparing a high-efficiency indium zinc sulfide photoanode

The indium zinc sulfide photoanode was generated by hydrothermal method, and the oxygen evolution promoter was modified by doping transition metal ions with cation exchange method and electrochemical deposition method, which solved the problem of low charge separation efficiency of indium zinc sulfide photoelectrode material and significantly improved its photoelectric conversion efficiency and activity.

CN115287696BActive Publication Date: 2025-03-14CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210890120.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-03-14
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

Indium zinc sulfide photoelectrode material has a slow carrier migration rate, high carrier recombination efficiency and large diffusion distance during the water decomposition process, resulting in low charge separation efficiency, limiting its practical application in decomposing water.

Method used

A multi-step method, including hydrothermal method to generate an indium zinc sulfide photoanode, doping transition metal ions using cation exchange method, and modifying the oxygen evolution promoter by electrochemical deposition to form a composite photoanode material.

Benefits of technology

The photoelectric conversion efficiency of the indium zinc sulfide photoanode is significantly improved, its activity is improved, and stable charge migration under the conditions of lower electron-hole recombination rates is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003767235510000011
    Figure HDA0003767235510000011
  • Figure HDA0003767235510000012
    Figure HDA0003767235510000012
  • Figure HDA0003767235510000013
    Figure HDA0003767235510000013
Patent Text Reader

Abstract

The present invention belongs to the technical field of optoelectronic materials, and discloses a method for preparing an efficient indium zinc sulfide photoanode. The present invention firstly prepares a transition metal-doped indium zinc sulfide photoanode by a one-step hydrothermal method, performs secondary transition metal doping on the indium zinc sulfide photoanode by a cation exchange method after annealing, and then modifies the surface of the transition metal-doped indium zinc sulfide photoanode with an oxygen evolution promoter by an electrodeposition method. Finally, an oxygen evolution promoter composite transition metal-doped indium sulfide nanosheet photoanode is obtained. The present invention can effectively solve the problems of serious electron-hole pair recombination and slow carrier transport capacity of indium zinc sulfide photoanode materials, and significantly improve the photoelectric conversion efficiency of indium zinc sulfide photoanode. The method proposed by the present invention has simple process, mild conditions, low cost, and obvious improvement effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectric materials, and mainly relates to a method for improving the activity of indium zinc sulfide photoanode by doping with transition metals and modifying oxygen evolution promoters at the same time. Background Art

[0002] Environmental pollution and resource shortage are two major problems we are facing now. They seriously violate the green and sustainable development strategy proposed by today's society. Therefore, it is urgent to seek a green and sustainable energy. Solar energy is a renewable energy source that is inexhaustible, and hydrogen energy is a clean energy source. The combustion and release of hydrogen energy will not produce polluting gases. Putting them together will give us what we need. Photoelectrochemical (PEC) water splitting is an effective method for clean hydrogen production. It not only utilizes the widely distributed solar energy, but also utilizes the electricity converted from various intermittent energy sources to produce hydrogen. It is considered to be one of the most promising technologies to alleviate environmental pollution and resource shortage problems. As an important component of the PEC water splitting device, the photoelectrode material should not only be able to effectively utilize solar energy to generate electron-hole pairs on its surface, but also exhibit good conductivity to achieve stable charge migration under low electron-hole recombination rates. Therefore, it is particularly important to prepare photoelectrode materials with excellent performance using cheap and simple methods.

[0003] Indium zinc sulfide (ZnIn2S4) is a semiconductor material with a narrow band gap (2.4-2.8 eV), low cost, non-toxic, stable chemical properties, and sensitivity to visible light. It has great potential as a photoelectrode material for PEC water splitting. However, indium zinc sulfide has disadvantages such as slow carrier migration rate, high carrier recombination efficiency, and large diffusion distance, which leads to low charge separation efficiency, thus restricting the practical application of indium zinc sulfide photoelectrodes in water splitting. Generally, metal doping and non-metal doping are used to improve the photoelectrocatalytic activity of indium zinc sulfide. However, the current modification of indium zinc sulfide is still far from satisfactory in improving the photoelectric conversion efficiency. Summary of the invention

[0004] In view of the defects of the above-mentioned indium zinc sulfide photoanode material, the present invention provides a preparation method for improving the photoelectric conversion efficiency of the indium zinc sulfide photoanode. The finally obtained indium zinc sulfide photoanode has good photoelectric activity, and the preparation method is simple and economical.

[0005] A method for preparing a high-efficiency indium zinc sulfide photoanode comprises the following steps:

[0006] (1) Mix the zinc salt and indium salt solutions, stir for a while, then add the sulfur source solution and mix evenly, and finally add the transition metal salt solution to be doped with ion I and stir evenly to obtain a precursor solution. Put the precursor solution into a high-pressure reactor, put FTO in, and perform a hydrothermal reaction. After the reaction, cool, wash, and dry.

[0007] (2) Annealing the photoanode obtained above in air, setting the annealing temperature and time, and immersing the photoanode material in step (1) in a transition metal salt solution to be doped with metal ion II to perform cation exchange to obtain a transition metal ion-doped indium zinc sulfide photoanode material.

[0008] After annealing in step (2), Zn and S vacancies are formed, and then cation exchange is performed to exchange the doped transition metal ions with the zinc in indium zinc sulfide, thereby further improving the photoactivity of indium zinc sulfide.

[0009] (3) The indium zinc sulfide photoanode material doped with transition metal ions in step (2) is modified with an oxygen evolution promoter on its surface by electrochemical deposition, thereby finally obtaining an indium zinc sulfide composite photoanode material.

[0010] Furthermore, in step (1), the zinc salt and the indium salt are one of nitrate, hydrochloride and sulfate, and the sulfur source is one of thiourea, thioacetamide and thiosemicarbazide;

[0011] The molar concentration ratios of zinc salt, indium salt and sulfur source in the precursor solution are 1:2:8 (sulfur source needs to be in excess); the molar concentration of the transition metal salt solution doped with metal ion I in the precursor solution is 4% to 20% of the molar concentration of the zinc salt.

[0012] The transition metal salt to be doped with metal ions in step (1) and step (2) is one of cadmium nitrate, cobalt nitrate, iron nitrate and nickel nitrate, but not limited to one of them;

[0013] The metal ions doped in step (1) and step (2) may be the same or different, and may be one or two or more of cadmium ions, cobalt ions, iron ions, and nickel ions. Preferably, the metal doped in step (1) is cadmium.

[0014] The molar concentration of the transition metal salt to be doped with metal ion I in the precursor solution is 4% to 20% of the molar concentration of the zinc source.

[0015] Furthermore, the hydrothermal temperature in step (1) is 160-200° C., and the hydrothermal time is 2-12 hours.

[0016] Furthermore, the annealing atmosphere in step (2) is air, the temperature is 100-500° C., and the time is 0.5-3 hours. If the annealing temperature is lower than 100° C., the electrode is not activated and the performance does not change.

[0017] Furthermore, the preferred oxygen evolution promoter described in step (3) is iron oxyhydroxide, and the deposition conditions are a metal salt aqueous solution with a concentration of 0.01 to 0.05 mol / L, an electrodeposition voltage of 0.1 to 0.5 V, and an electrodeposition time of 10 to 300 s.

[0018] Compared with the prior art, the effects and advantages of the present invention are:

[0019] The present invention directly generates indium zinc sulfide photoanode by one-step hydrothermal method, adopts immersion method for cation exchange, adopts electrochemical deposition method, and after the ion exchange method and electrochemical deposition method cooperate with each other, the activity of indium zinc sulfide photoanode is greatly improved, which is of great significance to the improvement and research of the activity of photoanode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a linear voltammetric scan curve of the cadmium ion-doped indium zinc sulfide photoanode modified with iron oxyhydroxide prepared in Example 1.

[0021] Figure 2 This is a linear voltammetric scan curve of the indium zinc sulfide photoanode co-doped with cadmium ions and cobalt ions modified with iron oxyhydroxide prepared in Example 2.

[0022] Figure 3 This is a linear voltammetric scan curve of the indium zinc sulfide photoanode co-doped with cadmium ions and nickel ions modified with iron oxyhydroxide prepared in Example 3.

[0023] Figure 4 This is the linear voltammetric scanning curve of the cadmium ion doped indium zinc sulfide photoanode prepared in Comparative Example 1.

[0024] Figure 5 This is a linear voltammetric scanning curve of the indium zinc sulfide photoanode prepared in Comparative Example 2 after annealing in an argon atmosphere.

[0025] Figure 6 This is the linear voltammetric scanning curve of the indium zinc sulfide photoanode doped with excess cadmium ions prepared in Comparative Example 3.

[0026] Figure 7 This is the linear voltammetric scanning curve of the calcium ion doped indium zinc sulfide photoanode prepared in Comparative Example 4. DETAILED DESCRIPTION

[0027] The following specific embodiments are used in conjunction with the accompanying drawings to explain in detail the technology and features of the present invention, but these embodiments are not intended to limit the scope of protection of the present invention. The scheme of synergistically improving the activity of indium zinc sulfide photoanode materials by doping with transition metals and modifying oxygen evolution co-catalysts is also applicable to other photoanode materials such as bismuth vanadate and iron oxide.

[0028] Example 1

[0029] (1) Mix zinc chloride and indium chloride in deionized water, stir for a while, then add thiourea and mix evenly, then add cadmium nitrate and stir evenly to obtain a precursor solution; in the precursor solution, the molar concentration ratio of zinc chloride: indium chloride and thiourea is 1:2:8 respectively; the molar concentration of cadmium nitrate in the precursor solution is 8% of the molar concentration of zinc chloride. Transfer the precursor solution to a high-pressure reactor with FTO already placed, and perform a hydrothermal reaction at a temperature of 200°C, a heat preservation time of 2h, and cooling, washing and drying at 60°C for 6h.

[0030] (2) Annealing the photoanode obtained in step (1) in air, maintaining it at 200° C. for 1 hour, and cooling it to room temperature to obtain an indium zinc sulfide photoanode. The obtained indium zinc sulfide-based photoanode is placed in a 0.1 mol / L cadmium nitrate solution for cation exchange at room temperature for 1 hour, and after the reaction is completed, it is washed and dried naturally to obtain a cadmium ion-doped indium zinc sulfide photoanode.

[0031] (3) Using electrochemical deposition, the ferric hydroxide is modified on the cadmium ion-doped indium zinc sulfide photoanode material obtained in step (2), the electrochemical deposition solution is a 0.01 mol / L ferrous sulfate solution, the electrochemical deposition time is 100 s, the electrochemical deposition voltage is 0.1 V, and nitrogen needs to be introduced for 30 minutes after the configuration to remove oxygen in the solution. Finally, the cadmium ion-doped indium zinc sulfide photoanode material modified with ferric hydroxide is obtained.

[0032] Indium zinc sulfide photoanode modified with iron oxyhydroxide: The indium zinc sulfide photoanode obtained in step (2) was not subjected to cation exchange doping, and other operations were the same as in Example 1.

[0033] Through the LSV curve ( Figure 1 ) It can be seen that the photocurrent density of indium zinc sulfide (ZnIn2S4) after annealing in air in step (2) is 0.97 mA / cm at 1.23 V relative to the reversible hydrogen electrode. 2 The photocurrent density of the FeOH-modified InZnS photoanode is 1.25 mA / cm 2 The photocurrent density of the cadmium ion-doped indium zinc sulfide photoanode is 4.37 mA / cm 2 , the cadmium ion doped indium zinc sulfide photoanode modified by iron oxyhydroxide is 4.89 mA / cm 2 Compared with the indium zinc sulfide photoanode, the performance is improved by 5.2 times, so the co-modification of doping and co-catalyst can significantly improve the activity of indium zinc sulfide.

[0034] Example 2

[0035] (1) Add zinc chloride and indium chloride to deionized water, mix, stir for a while, then add thiourea and mix evenly, finally add cadmium nitrate and cobalt nitrate, stir evenly, and obtain a precursor solution; the molar concentration ratio of zinc chloride: indium chloride and thiourea in the precursor solution is 1:2:8 respectively; the molar concentration of cadmium nitrate in the precursor solution is 4% of the molar concentration of zinc chloride; the molar concentration of cobalt nitrate is 4% of the molar concentration of zinc chloride. Transfer the precursor solution to a high-pressure reactor with FTO already placed, and perform a hydrothermal reaction at a temperature of 200°C and a holding time of 2h. Cool, wash and dry at 60°C for 6h.

[0036] (2) Annealing the photoanode obtained in step (1) in air, maintaining it at 200° C. for 1 hour, and cooling it to room temperature to obtain an indium zinc sulfide photoanode. The obtained indium zinc sulfide-based photoanode is placed in a 0.1 mol / L mixed solution of cadmium salt and cobalt salt at room temperature for cation exchange for 1 hour, and after the reaction is completed, it is washed and dried naturally. An indium zinc sulfide photoanode doped with cadmium and cobalt ions is obtained.

[0037] (3) Using electrochemical deposition, the ferric hydroxide is modified on the indium zinc sulfide photoanode material co-doped with cadmium ions and cobalt ions obtained in step (2), the electrochemical deposition solution is a 0.01 mol / L ferrous sulfate solution, the electrochemical deposition time is 100 s, the electrochemical deposition voltage is 0.1 V, and nitrogen needs to be introduced for 30 minutes after the configuration to remove oxygen in the solution. The cadmium and cobalt ion co-doped indium zinc sulfide photoanode material modified with ferric hydroxide is obtained.

[0038] According to the linear voltammetric scan, the photocurrent density of the indium zinc sulfide photoanode co-doped with cadmium ions and cobalt ions modified with iron oxyhydroxide is close to the photoanode performance obtained in Example 1 ( Figure 2 ), the photocurrent density of indium zinc sulfide after annealing in air in step (2) is 0.97 mA / cm at 1.23 V relative to the reversible hydrogen electrode 2 The photocurrent density of the cadmium and cobalt ion doped indium zinc sulfide photoanode is 4.2 mA / cm 2 , the cadmium-cobalt ion co-doped indium zinc sulfide photoanode modified by iron oxyhydroxide is 4.70 mA / cm 2 Compared with the indium zinc sulfide photoanode, the final performance is improved to 5 times, so transition metal doping and co-catalyst co-modification can significantly improve the activity of indium zinc sulfide.

[0039] Example 3

[0040] (1) Mix zinc chloride and indium chloride in deionized water, stir for a while, then add thiourea and mix evenly, finally add cadmium nitrate and stir evenly to obtain a precursor solution; the molar concentration ratio of zinc chloride: indium chloride and thiourea in the precursor solution is 1:2:8 respectively; the molar concentration of cadmium nitrate in the precursor solution is 8% of the molar concentration of zinc chloride. Transfer the precursor solution to a high-pressure reactor with FTO already placed, and perform a hydrothermal reaction at a temperature of 200°C and a holding time of 2h. Cool, wash and dry at 60°C for 6h.

[0041] (2) Annealing the photoanode obtained in step (1) in air, maintaining it at 200° C. for 1 hour, and cooling it to room temperature to obtain an indium zinc sulfide photoanode. The obtained indium zinc sulfide-based photoanode material is placed in a 0.1 mol / L nickel salt solution for cation exchange at room temperature for 1 hour, and after the reaction is completed, it is washed and dried naturally.

[0042] (3) Using electrochemical deposition, the ferric hydroxide is modified on the indium zinc sulfide photoanode material co-doped with cadmium ions and nickel ions obtained in step (2), the electrochemical deposition solution is a 0.01 mol / L ferrous sulfate solution, the electrochemical deposition time is 100 s, the electrochemical deposition voltage is 0.1 V, and nitrogen needs to be introduced for 30 minutes after the configuration to discharge oxygen in the solution. The ferric hydroxide-modified cadmium ion and nickel ion doped indium zinc sulfide photoanode material is obtained.

[0043] According to the linear voltammetric scan, the photocurrent density of the indium zinc sulfide photoanode co-doped with cadmium ions and nickel ions modified with iron oxyhydroxide is close to the photoanode performance obtained in Example 1 ( Figure 3 ), the photocurrent density of indium zinc sulfide after annealing in air in step (2) is 0.97 mA / cm at 1.23 V relative to the reversible hydrogen electrode 2 The photocurrent density of the cadmium and nickel ion doped indium zinc sulfide photoanode is 4.0 mA / cm 2 , the cadmium ion-doped indium zinc sulfide photoanode modified with iron oxyhydroxide is 4.69 mA / cm 2 Compared with the indium zinc sulfide photoanode, the performance is improved by nearly five times, so the co-modification of doping and co-catalyst can significantly improve the activity of indium zinc sulfide.

[0044] Comparative Example 1

[0045] (1) Same as Example 1;

[0046] (2) The photoanode obtained in step (1) was placed in a 0.1 mol / L cadmium salt solution for cation exchange for 1 hour. After the reaction was completed, it was washed, dried naturally, annealed in air, and maintained at 200° C. for 1 hour to obtain an indium zinc sulfide-based photoanode.

[0047] Through the LSV curve ( Figure 4 ) It can be seen that the photocurrent density of indium zinc sulfide after annealing is 0.97 mA / cm at 1.23 V relative to the reversible hydrogen electrode. 2 , the cadmium ion doped indium zinc sulfide photoanode is 2.3mA / cm 2 , relative to the current density of cadmium-doped indium zinc sulfide in Example 1 is 4.3 mA / cm 2 , the activity performance of indium zinc sulfide is poor when the order of change is changed.

[0048] Comparative Example 2

[0049] (1) Same as Example 1;

[0050] (1) Anneal the photoanode obtained in step (1) in argon gas at 200° C. for 1 h.

[0051] Through the LSV curve ( Figure 5 ) It can be seen that the photocurrent density of InZnS annealed in argon is 0.3 mA / cm at 1.23 V vs. reversible hydrogen electrode. 2 Compared with the indium zinc sulfide annealed in air in Example 1, the activity of indium zinc sulfide annealed in argon is greatly reduced.

[0052] Comparative Example 3

[0053] (1) Mix zinc chloride and indium chloride in deionized water, stir for a while, then add thiourea and mix evenly, and finally add cadmium nitrate and stir evenly to obtain a precursor solution. The molar concentrations of zinc chloride, indium chloride and thiourea in the precursor solution are 1:2:8 respectively; the molar concentration of cadmium nitrate in the precursor solution is 25% of the molar concentration of zinc chloride. The precursor solution is transferred to a high-pressure reactor with FTO already placed, and a hydrothermal reaction is carried out, followed by cooling, washing and drying.

[0054] (2) Same as Example 1.

[0055] Through the LSV curve ( Figure 6 ) It can be seen that the excess cadmium ion doped indium zinc sulfide photoanode is 2.36mA / cm 2 Compared with the indium zinc sulfide photoanode doped with no excess cadmium ions, the activity of indium zinc sulfide has a significant decrease.

[0056] Comparative Example 4

[0057] (1) Mix zinc chloride and indium chloride in deionized water, stir for a while, then add thiourea solution and mix evenly, finally add calcium salt and stir evenly to obtain a precursor solution; the molar concentrations of zinc chloride, indium chloride and thiourea in the precursor solution are 1:2:8 respectively; the molar concentration of calcium salt in the precursor solution is 8% of the molar concentration of zinc chloride. Transfer the precursor solution to a high-pressure reactor with FTO already placed, perform hydrothermal reaction, cool, wash and dry.

[0058] (2) Anneal the photoanode obtained in step (1) in air at 200° C. for 1 h. Place the obtained indium zinc sulfide-based photoanode material in a 0.1 mol / L calcium salt solution for cation exchange for 1 h, wash it after the reaction is complete, and dry it naturally.

[0059] Through the LSV curve ( Figure 7 ) It can be seen that the photocurrent density of indium zinc sulfide after annealing is 0.97 mA / cm at 1.23 V relative to the reversible hydrogen electrode. 2 , the calcium ion doped indium zinc sulfide photoanode is 1.77mA / cm 2 , compared with the cadmium-doped indium zinc sulfide photoanode, the activity of calcium-doped indium zinc sulfide is far inferior.

[0060] The above is only the best specific implementation method of the present invention, but the protection scope of the present invention is not limited to this. Any technician familiar with the present technology can make equivalent replacements or changes according to the technical scheme and concept of the present invention within the technical scope of condensation of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high-efficiency indium zinc sulfide photoanode, characterized in that: The preparation process includes the following: (1) uniformly mixing zinc salt, indium salt and sulfur source solution, adding transition metal salt to be doped with metal ion I, stirring evenly to obtain a precursor solution; placing the precursor solution in a high-pressure reactor, placing FTO in the reactor, performing a hydrothermal reaction, cooling to room temperature, taking out the FTO, washing and drying; the molar concentration of the transition metal salt solution doped with metal ion I in the precursor solution is 4% to 20% of the molar concentration of the zinc salt; (2) annealing the photoanode obtained in step (1), and then immersing the photoanode in a transition metal salt solution to be doped with metal ion II for cation exchange treatment, washing and drying naturally after completion; the metal ion I to be doped and the metal ion II to be doped are one or two or more of cadmium ion, cobalt ion, iron ion and nickel ion; the annealing atmosphere is air, the annealing temperature is 100 to 500° C., and the annealing time is 0.5 to 3 h; (3) Electrochemically depositing and modifying an oxygen evolution promoter on the surface of the photoanode obtained in step (2) to finally obtain an indium zinc sulfide composite photoanode, wherein the oxygen evolution promoter is iron oxyhydroxide.

2. The method for preparing a high-efficiency indium zinc sulfide photoanode according to claim 1, characterized in that: The zinc salt and indium salt in step (1) are one of nitrate, hydrochloride and sulfate, and the sulfur source is one of thiourea, thioacetamide and thiosemicarbazide.

3. The method for preparing a high-efficiency indium zinc sulfide photoanode according to claim 1, characterized in that: The metal ions I to be doped are cadmium ions.

4. The method for preparing a high-efficiency indium zinc sulfide photoanode according to claim 1, characterized in that: The molar concentration ratios of zinc salt, indium salt and sulfur source in the precursor solution are 1:2:8, respectively.

5. The method for preparing a high-efficiency indium zinc sulfide photoanode according to claim 1, characterized in that: The hydrothermal reaction temperature in step (1) is 160-200° C., and the hydrothermal reaction time is 2-12 hours.

6. The method for preparing a high-efficiency indium zinc sulfide photoanode according to claim 1, characterized in that: The deposition conditions in step (3) are: in a 0.01-0.05 mol / L metal salt solution, the electrodeposition voltage is 0.1-0.5 V, and the deposition time is 10-300 s.

Citation Information

Patent Citations

  • Photocatalyst for preparing hydrogen and sulphur by decomposing hydrogen sulfide and preparation method thereof

    CN101927173A

  • Preparation method of titanium carbide composite indium-zinc sulfide photo-anode

    CN110735151A